The Existence of Workers' Rights to Job Loss Insurance in the Event of Ter-mination of Employment Due to Violation of Collective Agreements - Wijayanti, Lini; Wijayanti, Asri; Miarsa, Fajar Rachmad Dwi (Institute for Law and Economics Studies, 2025)
The Job Loss Insurance Program is a social protection program aimed at workers who lose their jobs due to termination of employment (PHK). The benefits of this program include cash assistance, job training, and job market information, and are regulated by Law No. 6 of 2023 and Government Regulation No. 37 of 2021, which was amended to Government Regulation No. 6 of 2025. This study aims to analyze the existence of the right to Job Loss Insurance for workers who experience termination of employment due to violations of collective labor agreements, which, in practice, lack clear legal certainty. The method used in this study is a normative legal approach based on legislation and conceptual analysis. The findings reveal disparities in legal protection and normative uncertainty, which may impact workers' access to unemployment insurance benefits. Therefore, harmonization of policies and regulations is necessary to provide legal certainty and inclusive, fair protection for all workers